Implementation of the Merdeka Curriculum - Hamzah Sutisna (CV Projurnal Mitra Publikasi, 2025)
This research aims to identify and find out how the implementation of the Merdeka Curriculum program and its implications are implemented in various schools. This research uses a library research approach or through literature study. The data collection technique uses documentation by recording data from several book sources and other documents such as the official media of the Ministry of Education, Culture and Research and also other sources of information. This research explains and describes how the implementation of the Merdeka Curriculum itself and its implications have been implemented in various educational units. The findings reveal that the implementation of the curriculum in various educational units has been carried out optimally and is ongoing, although in its implementation there are still many obstacles and shortcomings. The key to the shortcomings of the implementation of this Merdeka Curriculum lies in the awareness of students as well as schools and teachers who must have the desire to make changes, as well as the clarity and real assistance from the government, especially the relevant education units, for the implementation of the Merdeka Curriculum program run by the Ministry of Education, Culture, Research and Technology.